1986
DOI: 10.1099/0022-1317-67-11-2501
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Wild-type Pathogenicity to an Attenuated DNA Polymerase Mutant of Herpes Simplex Virus Type 1

Abstract: SUMMARYThe drug-resistant variant, RSC-26, which was derived from the herpes simplex virus type 1 wild-type strain SC16, expresses an altered DNA polymerase and has reduced pathogenicity in animal models. To determine whether the attenuation in pathogenicity was due solely to mutation in the polymerase gene, a fragment of the wild-type gene was cloned, transferred into the genome of RSC-26 and recombinants were isolated. Three recombinants examined had similar properties to wild-type virus with respect to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…This is particularly important in the consideration of BHV 1 vaccine design and the use of modifiedlive and recombinant modified-live virus vaccines. It has been shown with human herpesviruses that recombination in vivo can generate lethal recombinants from avirulent strains [12,13,15,35]. Although we did not see evidence, based on RE patterns, of recombinants in this study, further investigations are needed to confirm whether BHV 1 can form recombinants in vivo.…”
Section: Discussioncontrasting
confidence: 73%
“…This is particularly important in the consideration of BHV 1 vaccine design and the use of modifiedlive and recombinant modified-live virus vaccines. It has been shown with human herpesviruses that recombination in vivo can generate lethal recombinants from avirulent strains [12,13,15,35]. Although we did not see evidence, based on RE patterns, of recombinants in this study, further investigations are needed to confirm whether BHV 1 can form recombinants in vivo.…”
Section: Discussioncontrasting
confidence: 73%
“…A polymerase mutant RSC26 derived from a parent strain SC16 was converted to a drugsensitive phenotype by marker rescue using a fragment of the wild type polymerase gene. 41 The reversion to a drug sensitive phenotype was accompanied by restoration of wild type virulence.…”
Section: Dna Polymerase Mutantsmentioning
confidence: 99%
“…Any alteration in a virus gene that impairs replication in vitro will also affect the performance of the virus in vivo and therefore all essential genes could be considered as 'virulence' genes (Darby et al, 1984;Larder et al, 1986). In HSV-1 it has been clearly demonstrated that there are several genes whose expression is not required for multiplication in dividing cells in tissue culture, presumably because a cellular homologue can compensate for the HSV gene.…”
Section: Introductionmentioning
confidence: 99%